2004
DOI: 10.1111/j.1600-4469.2004.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of impact object characteristics on impact force and force absorption by mouthguard material

Abstract: Most impact force and impact energy absorption tests for mouthguards have used a steel ball in a drop-ball or the pendulum device. However, in reality most sports-related trauma is caused by objects other than the steel ball, e.g. various sized balls, hockey puck, or bat or stick. Also, the elasticity, the velocity and the mass of the object could change the degree and the extent of injuries. In this study, we attempted to measure the impact force from actual sports equipment in order to clarify the exact mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 24 publications
4
98
3
2
Order By: Relevance
“…In another study, it was mentioned that it is realistic and appropriate to select more than one sensor type and impact object to assess the effectiveness of a mouthguard material 11) . Results of the present study agreed with the aforementioned claims of Takeda et al 11,20) . Sports that involve the use of sticks like ice hockey, field hockey, shinty, bandy, and hurling are good examples where impact objects are different from round types such as the hockey puck or ball.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In another study, it was mentioned that it is realistic and appropriate to select more than one sensor type and impact object to assess the effectiveness of a mouthguard material 11) . Results of the present study agreed with the aforementioned claims of Takeda et al 11,20) . Sports that involve the use of sticks like ice hockey, field hockey, shinty, bandy, and hurling are good examples where impact objects are different from round types such as the hockey puck or ball.…”
Section: Discussionsupporting
confidence: 82%
“…In a study by Takeda et al, it was reported that while mouthguard materials were effective in reducing the impact force of any impact object, shock absorption ability depended on the object type 20) . In another study, it was mentioned that it is realistic and appropriate to select more than one sensor type and impact object to assess the effectiveness of a mouthguard material 11) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Интерес к экспериментальному исследованию воздействия на органы и ткани челюстно-лицевой области при использовании спортивных капп проявляли многие авторы [15,16,18,19]. Так, в работе [14] произведён биомеханический анализ напряженно-деформированного состояния зуба при взаимодействии с мячом, движущимся со скоростью 1 м/с.…”
Section: биомеханические аспекты применения спортивных зубных шинunclassified